2013
DOI: 10.1007/s10620-013-2759-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes After Single-Balloon Enteroscopy: Are They Any Different from Double-Balloon Enteroscopy for Vascular Lesions?

Abstract: Obscure GI bleeding is uncommon, accounting for approximately 5 % of all GI bleeding episodes [1]. With the advent of capsule endoscopy and introduction of balloon enteroscopy to the United States in 2004, endoscopic visualization of the small bowel has become feasible and successful. Double-balloon enteroscopy (DBE) is associated with diagnostic yields of approximately 50-60 %, which exceed 70 % in patients with obscure gastrointestinal bleeding (OGIB) [2]. Performance of video capsule endoscopy (VCE) prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…This technology has largely replaced conventional barium studies and intraoperative enteroscopy 15. Although less data has been published with regard to single balloon enteroscopy (SBE) outcomes compared with double balloon enteroscopy (DBE), as it is a newer technology, multiple studies have shown the two devices to be comparable 12 13 14 16 17 18 19 20 21. Our institution uses SBE for evaluation and therapeutic intervention of suspected small-bowel disorders.…”
Section: Introductionmentioning
confidence: 99%
“…This technology has largely replaced conventional barium studies and intraoperative enteroscopy 15. Although less data has been published with regard to single balloon enteroscopy (SBE) outcomes compared with double balloon enteroscopy (DBE), as it is a newer technology, multiple studies have shown the two devices to be comparable 12 13 14 16 17 18 19 20 21. Our institution uses SBE for evaluation and therapeutic intervention of suspected small-bowel disorders.…”
Section: Introductionmentioning
confidence: 99%